Methods Used by Fourth Graders when Responding to Number Sense-Related Questions - Wei, Huang, Jia-; Ching, Yang, Der- (American Journal of Education and Learning, 2018)
This study examined the methods used by fourth graders when answering number sense-related questions. Eighth fourth graders who were classified as high, medium, and low achievers in mathematics were recruited from three public elementary schools in south Taiwan. Semi-structured interviews were conducted with all students, in which they responded to a series of number sense-related questions. The findings showed that all students tended to use rule-based methods to solve the questions. However, low and medium achievers were more inclined than high achievers to use rule-based methods to solve the problems. Additionally, the findings suggest that students’ thinking is limited to memorizing the methods they have learned in schools; thus, they cannot use meaningful approaches to solve problems.